Perceptions on the importance of gerontological education by teachers and students of undergraduate health sciences - Mendoza-Núñez, Víctor Manuel (BioMed Central, 2007)
BACKGROUND: The main challenge of higher education institutions throughout the world is to develop professionals capable of understanding and responding to the current social priorities of our countries. Given the utmost importance of addressing the complex needs of an increasingly elderly population in Mexico, the National Autonomous University of Mexico has systematically incorporated modules dealing with primary gerontological health care into several of its undergraduate programs in health sciences. The objective of this study was to analyze teacher's and student's perceptions about the current educational practices on gerontology. METHODS: A cross-sectional study was carried out with a sample of 26 teachers and 122 undergraduate students. Subjects were administered interviews and responded survey instrument. RESULTS: A vast proportion of the teachers (42%) reported students' attitudes towards their academic training as the most important factor affecting learning in the field of gerontology, whereas students reported that the main problems of education in gerontology were theoretical (32%) and methodological (28%). In addition, 41% of students considered education on ageing matters as an essential element for their professional development, as compared to 19% of teachers (p < 0.05). CONCLUSION: Our findings suggest that the teachers' perceptions about the low importance of education on ageing matters for the professional practice of health sciences could be a negative factor for gerontology teaching.